Mapping cultural ecosystem services in Aruba the Southern Caribbean - Soberón-Forsberg, Vanessa Sofía (2021)
The objective study was to map cultural ecosystem services (aesthetic appreciation and recreation) in Aruba, from tourists’ point of view. The Public participation Geographical Information System was used. Aruba has two types of visitors: Stay-Over visitors (who spend at least one night in Aruba) and Cruise visitors (those who do not spend the night). Data was obtained by interviewing tourists using Public Participatory Geographic Information System in October and November 2016 and March 2017. The data was used to determine tourists’ aesthetic and recreational hot spots (areas with an abundance of events) and then to compare Cruise visitors’ hot spots with Stay-Over visitors’ hot spots. Then, tourists’ hot spots were compared with the local resident’s hot spots. The residents’ data was obtained from a previous study. Tourists and local citizens indicate that the California Lighthouse was an aesthetic hotspot and that Eagle Beach was a recreational hotspot. Tourists and local citizens disagree about Palm Beach and Arikok National Park aesthetic value and about Surfside Beach recreational value. It is concluded that Eagle Beach, Palm Beach and California Lighthouse are areas of great interest and that there are similarities and differences in stakeholder perception of Aruba's aesthetic and recreational hotspots.